Study on Gene Action of Yield and its Attributes in Rice (Oryza sativa L.) under Phosphorus-deficient Conditions using Haymans Approach - Vishnupriya, S.; Roy, S. K.; Sen, Shubhrajyoti; Kundu, Avijit; Mitra, Biplab; Mukhopadhyay, Dibyendu; Umamaheswar, Naderla; Vasanth, V.; Antony, Bonipas (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during kharif (July, 2022–January, 2023) at the Instructional Agricultural Farm, Uttar Banga Krishi Vishwavidhyalaya, Cooch Behar, West Bengal, India to measure gene action and inheritance of yield and its attributing characteristics of rice under phosphorus-deficient soil conditions. The experimental material comprised eight diverse rice genotypes and their 28 direct crosses grown under phosphorus-deficient soil conditions in a randomized block design with three replications. Data on 14 quantitative characters were recorded and tested using the t² test. Regression of Wr on Vr and genetic components of variance were estimated, and graphical analysis was performed using Hayman’s methodology. Non-significance of the t² test for all characters implied that there was no epistatic gene interaction. Estimation of genetic components revealed the presence of both additive and non-additive genes. The graphical approach indicated over-dominance gene action for the characters, flag leaf length, flag leaf width, no. of panicles plant-1, and grain yield, whereas the remaining ten characters exhibited partial dominance. The rice genotype, CR Sugandh Dhan 909, exhibited dominance for phosphorus uptake and Paolum Sali for grain yield. Under phosphorus-deficient conditions, dominant alleles and significant additive gene effects facilitated early-generation fixability of traits. Overdominance played a significant role in certain traits like flag leaf dimensions and grain yield, indicating efficient selection possibilities in later generations.